PERANCANGAN APLIKASI SISTEM INFORMASI PEMBELIAN DAN PENJUALAN ALAT TULIS KANTOR - Sifa Fauziah (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan)
Rapid technological advances are currently demanding every store and company to create a business system that is more effective and efficient and good and fast service to every consumer. Therefore the application of information systems is needed that can help expedite the work process in the business system. Toko Ratu Alfamaz is a business entity engaged in trade. In improving and expediting the process of the purchasing system and the sales system, Toko Ratu Alfamaz needs a computerized system. because the system used is a conventional system. So that in running the system of buying and selling office stationery there are problems that often occur such as errors in calculating the total cost of purchase or total sales, the slow process of recording and searching data and the process of making reports requires a long time and the resulting inaccurate. Based on the conditions in Ratu Alfamaz's store, the authors designed an application system for purchasing and selling office stationery using the visual basic 6.0 programming language. The method used in this study is to use the method of observation, interviews and literature. And for software development methods using the waterfall method. The application of this information system is expected to reduce the level of errors that exist and help improve services to consumers to be more effective and efficient.